The Method of Total Erythrocyte and Leukocyte Counting in Raptors at Wildlife Rescue Centre (WRC) Jogja - Hardian, Andreas Bandang; Nugrahani, Warih Pulung Nugrahani; Rahmawati, Irhamna Putri Rahmawati; Megarani, Dorothea Vera Megarani (Faculty of Veterinary Medicine Universitas Brawijaya, 2020)
Most of raptor species rehabilitated for conservation purpose at WRC Jogja are eagles. Annually, we perform general raptor examination involving conventional routine hematologic examination. However, low sample quality and over dense blood cell population during total erythrocyte and leukocyte counting were deemed as obstacles. This study aimed to give wider insight in how total erythrocyte and leukocyte counting was performed at WRC Jogja to overcome those obstacles. Firstly, handling and restraint were done physically adapting the Aba method. One-to-two half millilitres of blood was collected from the ulnar vein using 3-ml-syringe with 24-gauge-needle which was then preserved in an EDTA-containing tube and proceeded to subsequent method no more than 3 hours after collection. No hypovolemic shock was observed. During total erythrocyte and leukocyte counting using Neubauer-ruled counting chamber, we modified the dilution factor to be 250-fold and 50-fold respectively. This method yielded a countable cell density and can be applied in other species in similar condition.